Views of pupils from selected elementary and secondary grammar schools of assessment in biology lessons with the focus on formative assessment - Rokos, Lukáš; Lišková, Jana; Váchová, Lucie; Cihlářová, Magdalena; Chadová, Magdalena; Strapková, Jana (Scientia in educatione, 2019)
Formative assessment has become a frequently discussed evaluation approach which can help enhance the students‘ performance in science subjects. The ASSIST-ME was a European project focused on helping the effective implementation of formative and summative assessment in inquiry-based learning in science and mathematics in elementary and secondary schools in different European educational environments. It also sought to verify the readiness of teachers and teacher trainees to use formative assessment in teaching. This paper presents the results of the probe investigating the experience of students from selected elementary and grammar schools in the region of South Bohemia with various assessment methods in biology. The emphasis was put on the students‘ knowledge and personal experience with formative assessment. Data from 1 848 respondents were obtained by a questionnaire survey. The survey has proved that the summative assessment is prevailing assessing approach at the selected schools but the students find this approach satisfactory and prefer it to other assessing approaches. Students also stated that they had generally been examined in written form with focus on their content knowledge. Approximately half of the respondents claimed they had had personal experience with the formative assessment.